Long term follow-up study for abdominal sacrocolpopexy/sacrohysteropexy - Puri, Sapna; Jaggi, Rohini; Sunil, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pelvic organ prolapse is common in women and 7-9% undergo surgical repair. Abdominal sacrocolpopexy and sacrohysteropexy is the most durable operation for vault prolapse and Nulliparous prolapse respectively. The objectives of this study were to describe Anatomic and symptomatic outcomes up to 5 years after abdominal sacrocolpopexy or sacrohysteropexy. Methods: This study was conducted in ASCOMS hospital for a cohort of patients who underwent abdominal sacrocolpopexy (ASC) or sacrohysteropexy (ASH) in 2 years (2013-2015) and follow up done for a period of 5 years from 2015-2019. These patients were evaluated for subjective and objective outcomes following ASC and ASH. women completed questionnaires and were examined in gynaecology clinic. Prospective follow up study using standarised examination with pelvic organ prolapse quantification system (POP-Q) and questionnaires Results: In the present study, there was low incidence of intraoperative and postoperative complications as well as long term complications were significantly low. The anatomical cure rate and patient satisfaction rate was both 100%. Conclusions: Abdominal sacrocolpopexy for vault prolapse and sacrohysteropexy for Nulliparous prolapse is safe and effective method and is considered gold standard for treatment of Apical compartment prolapse.